2019
DOI: 10.1080/23766808.2019.1659022
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal differences in alpha, beta and functional diversity of an amphibian community in a biodiversity hotspot

Abstract: Biodiversity research along altitudinal gradients can provide us with new insights into conservation and human impacts. In this context, amphibians are a useful and important group due to their rapid response to environmental changes, severely threatened status and because of the gaps in our knowledge of their ecology, especially in tropical forests. Here, we investigate the differences in amphibian communities along an altitudinal gradient with the aim to understand how different groups respond to altitude an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
1
10
0
3
Order By: Relevance
“…Altitude was found to be a strong predictor of species richness and abundance at the sample level, with fewer species and fewer individuals detected per sample at higher elevations; notably observed in some of the highest sampling locations in the regenerating forest, and especially in the native community of Shintuya. This pattern of species richness and abundance decline with increasing elevation has been shown in other amphibian studies (Khatiwada et al, 2019; Villacampa et al, 2019). Despite the role of altitude in the amphibians found in our nocturnal transects, it is important to note that this effect of altitude was found only at the sample level, as the models are trying to explain the species richness and abundance found within each survey carried out across study locations.…”
Section: Discussionsupporting
confidence: 85%
“…Altitude was found to be a strong predictor of species richness and abundance at the sample level, with fewer species and fewer individuals detected per sample at higher elevations; notably observed in some of the highest sampling locations in the regenerating forest, and especially in the native community of Shintuya. This pattern of species richness and abundance decline with increasing elevation has been shown in other amphibian studies (Khatiwada et al, 2019; Villacampa et al, 2019). Despite the role of altitude in the amphibians found in our nocturnal transects, it is important to note that this effect of altitude was found only at the sample level, as the models are trying to explain the species richness and abundance found within each survey carried out across study locations.…”
Section: Discussionsupporting
confidence: 85%
“…Several empirical studies on anuran species richness in different tropical and subtropical mountainous regions worldwide have documented from 16 to 60 species (Carvalho‐Rocha et al, 2021; Giaretta et al, 1999; Goyannes‐Araújo et al, 2015; Malonza & Veith, 2012; Siqueira et al, 2011, 2021; Villacampa et al, 2019; Zancolli et al, 2014). In our study, we found 70 anuran species at Poços de Caldas Plateau region.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should focus on separating the beetle communities into functional groups, which would be useful for understanding some of the factors likely driving the observed diversity patterns, and their potential conservation implications 63 . We need to analyse other dimensions of the beetle biodiversity as functional and phylogenetic metrics to unravel the factors and mechanisms driving membership of these communities across these mountains.…”
Section: Discussionmentioning
confidence: 99%